(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
The proposed diagnostic method makes it possible to assess the density of alveolar bone tissue by measuring the speed of passage of an ultrasonic wave (ultrasound) of 2.5 MHz in the studied area of the alveolar process of the upper jaw and the alveolar part of the lower jaw. Echosteometry makes it possible to determine the density of the alveolar bone of the jaws with a high degree of accuracy, which makes it possible to recommend this research method for diagnosing the mineral density of the alveolar bone and predicting possible recurrence of anomalies in the position of the teeth after completion of orthopedic treatment